Evaluation of the Effects of Harmine on β-cell Function and Proliferation in Standardized Human Islets Using 3D High-Content Confocal Imaging and Automated Analysis - Title, Alexandra C.; Karsai, Maria; Mir-Coll, Joan; Grining, Özlem Yavas; Rufer, Chantal; Sonntag, Sebastian; Forschler, Felix; Jawurek, Sayro; Klein, Thomas; Yesildag, Burcak (Frontiers in Endocrinology, 2022)
Restoration of β-cell mass through the induction of proliferation represents an attractive therapeutic approach for the treatment of diabetes. However, intact and dispersed primary islets suffer from rapidly deteriorating viability and function ex vivo, posing a significant challenge for their experimental use in proliferation studies. Here, we describe a novel method for the assessment of compound effects on β-cell proliferation and count using reaggregated primary human islets, or islet microtissues (MTs), which display homogeneous size and tissue architecture as well as robust and stable functionality and viability for 4 weeks in culture. We utilized this platform to evaluate the dose-dependent short- and long-term effects of harmine on β-cell proliferation and function. Following compound treatment and EdU incorporation, islet MTs were stained and confocal-imaged for DAPI (nuclear marker), NKX6.1 (β-cell marker), and EdU (proliferation marker), allowing automated 3D-analysis of number of total cells, β-cells, and proliferating β- and non-β-cells per islet MT. In parallel, insulin secretion, intracellular insulin and ATP contents, and Caspase 3/7 activity were analyzed to obtain a comprehensive overview of islet MT function and viability. We observed that 4-day harmine treatment increased β- and non-β-cell proliferation, NKX6.1 expression, and basal and stimulated insulin secretion in a dose-dependent manner, while fold-stimulation of secretion peaked at intermediate harmine doses. Interestingly, 15-day harmine treatment led to a general reduction in harmine’s proliferative effects as well as altered dose-dependent trends. The described methodology provides a unique tool for in vitro high-throughput evaluation of short- and long-term changes in human β-cell proliferation, count and fraction along with a variety of functional parameters, in a representative 3D human islet model.